Non West modernist past : on architecture & modernities - Lim, William Siew Wai, 1932-; Chang, Jiat-Hwee. (World Scientific Pub., 2012)
"This book is an essential resource for understanding architectural modernism outside its "western" regions and mindsets. Its in-depth discussion and insights will be invaluable to specialists, academics and graduate students. It is also comprehensive enough to be used as a textbook for undergraduate students, and general enough for practitioners and the curious general reader."--P. [4] of cover.